PENGARUH RETURN ON ASSET (ROA), EARNING PER SHARE (EPS) DAN TOTAL ASSET TURNOVER (TATO) TERHADAP HARGA SAHAM PADA PT ASTRA OTOPARTS TBK PERIODE 2012-2023 - Heni Syafitri, Revi; Faisal (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Return On Asset (ROA), Earning Per Share (EPS) and Total Asset Turnover (TATO) on Stock Prices at PT Astra Otoparts Tbk for the period 2012-2023. The method used in this research is descriptive quantitative method. In this study using secondary data. Sampling using purposive sampling technique. The data analysis method used is multiple regression analysis, t-test hypothesis testing, f-test and determination coefficient test (R2) using the SPSS version 25 approach. The research population is the annual financial report published on PT Astra Otoparts Tbk. The results of the t test show that ROA has a sig value (0.011 <0.05) and the tcount> ttable value (3.269> 2.26216) this means that partially ROA has a significant effect on stock prices. EPS has a Sig value (0.097> 0.05) and a tcount value < ttable (-1.878 < 2.26216). This means that partially EPS has no significant effect on Stock Price. TATO has a Sig value (0.081> 0.05) and a tcount value < t table (-1.999 < 2.26216). This means that partially TATO has no significant effect on Stock Price. While the research on the results of the f-test shows that the sig value. 0.020 <0.05 and the value of fcount 5.902> ftabel 4.07. This means that ROI, EPS and TATO simultaneously have a significant effect on Stock Prices. The test results of the Coefficient of Determination show the value of Adjust.